The Relationship Between Work Motivation, Job Satisfaction, and Turnover Intention in Nurses - Pradiptha, I Dewa Agung Gde Fanji; Kio, Alfiery Leda; Adi, Nyoman Putri Sri; Purwanto, Ika; Redho, Ahmad (Babali Publisher, 2023)
Background: Human resources are the main resource in a hospital. Nurses are the main and most important resource and the tip spearhead in every nursing service activity in the hospital. It is demanding nursing as a profession to improve intellectual abilities, abilities interpersonal, and moral so that in achieving this, the nurse requires strong motivation both from within and outside the nurse. Nurses who have good work motivation can influence the increase nurse job satisfaction so as to reduce nurse turnover intention. This study aims to analyses the relationship of work motivation to job satisfaction and turnover intention of nurses at Klungkung Hospital. Methods: This study uses a correlational research design approach cross sectional. The sample used was 139 implementing nurses with stratified random sampling technique. Results: Correlation test results show motivation to work with Job satisfaction has a strong and positive relationship (r = 0.623 and p = 0.0005), work motivation with turnover intention has a weak relationship and negative pattern (r = -0.035 and p = 0.680) and job satisfaction with turnover intention shows a moderate relationship and has a negative pattern (r = -0.252 and p = 0.003). The results of the PLS analysis show that work motivation is related to satisfaction work (t = 12.0422), work motivation related to turnover intention (t = 2.3796) and job satisfaction related to turnover intention (t = 4.0125). Conclusions: Work motivation good impact on increasing job satisfaction and decreasing turnover nurse intentions. Future researchers should examine more of these factors affect turnover intention.